Encyclopedia of global change : environmental change and human society. Volume 2 - Goudie, Andrew ; Cuff, David J. (Oxford University Press, 2020)
The Encyclopedia synethsizes current knowledge on natural and human-made changes in the Earth's physical , chemical, and biological systems and the effects of these changes on society. Areas such as altered ecosystems, climate change, food supply, water production and consumption, population, and the political impact of global change are covered in detail. And the clearly written articles also include responses to global modification, agreements and associations, institutions, policies, biographies, and case studies. Enhanced by 1,500 illustrations, extensive cross-references, bibliographies, and an index, the Encyclopedia of Global Change links essential knowledge across many fields-geography, geology, geophysics, atmospheric science, political science, economics, technology, and others-in a resource that is both accessible and authoritative. The jargon-free language makes it an excellent work for the professional scholar as well as the interested general reader.